Metagenomic and Microscopic Analysis of Magnetotactic Bacteria in Tangyin Hydrothermal Field of Okinawa Trough - Chen, Si; Yu, Min; Zhang, Wenyan; He, Kuang; Pan, Hongmiao; Cui, Kaixuan; Zhao, Yicong; Zhang, Xiao-Hua; Xiao, Tian; Zhang, Wuchang; Wu, Long-Fei (Frontiers in Microbiology, 2022)
Magnetotactic bacteria (MTB) have been found in a wide variety of marine habitats, ranging from intertidal sediments to deep-sea seamounts. Deep-sea hydrothermal fields are rich in metal sulfides, which are suitable areas for the growth of magnetotactic bacteria. However, magnetotactic bacteria in hydrothermal fields have never been reported. Here the occurrence of MTB in sediments from the Tangyin hydrothermal field was analyzed by 16S rRNA gene amplicon analysis, metagenomics and transmission electron microscopy. Sequencing 16S rRNA gene yielded a total of 709 MTB sequences belonging to 20 OTUs, affiliated with Desulfobacterota, Alphaproteobacteria, and Nitrospirae. Three shapes of magnetofossil were identified by transmission electron microscopy: elongated-prismatic, bullet-shaped, and cuboctahedron. All of these structures were composed of Fe3O4. Totally 121 sequences were found to be homologous to published MTB magnetosome-function-related genes, and relevant domains were identified. Further analysis revealed that diverse MTB are present in the Tangyin hydrothermal field, and that multicellular magnetotactic prokaryotes (MMPs) might be the dominant MTB. And the MTB of Desulfobacterota and Nitrospirae here shown evolutionarily unique compared with known MTB.